2017
DOI: 10.1016/j.bandl.2017.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of the lexicality effect in children

Abstract: The comparison of words and pseudowords has been extensively used in adult neuroimaging studies to inform neurocognitive models of reading but has rarely been used to inform models of reading acquisition. Using a rhyming judgment task, the current study examined age-related differences in the spelling to sound mapping mechanisms involved in word and pseudoword reading. We hypothesized a developmental increase in specialization of the brain mechanisms engaged for word and pseudoword processing. Consistent with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 51 publications
2
8
0
1
Order By: Relevance
“…The PSQI is a self-rated questionnaire that assesses sleep quality and sleep disturbances over the past month 70 . It has been well validated and is widely used in both clinical and nonclinical settings 71,72 . It has demonstrated high levels of internal consistency and construct validity, with a Cronbach's alpha of 0.8 73 .…”
Section: Study Variables Pittsburgh Sleep Quality Index (Psqi)mentioning
confidence: 99%
See 1 more Smart Citation
“…The PSQI is a self-rated questionnaire that assesses sleep quality and sleep disturbances over the past month 70 . It has been well validated and is widely used in both clinical and nonclinical settings 71,72 . It has demonstrated high levels of internal consistency and construct validity, with a Cronbach's alpha of 0.8 73 .…”
Section: Study Variables Pittsburgh Sleep Quality Index (Psqi)mentioning
confidence: 99%
“…While this application remains controversial 82 , several neuroimaging studies on developing brains have not only shown neuroanatomical differences between adults but also demonstrated valid neuroimaging results for children using the adult template 71,[83][84][85] . Moreover, the standard adult SPM template enables us to compare or combine the results of previous studies conducted in adults or across different age groups 72,86,87 .…”
mentioning
confidence: 99%
“…(2010)−45−57−12Stimuli: primesStevens et al. (2017)−52−49−13Stimuli: visual contentWeiss and Booth (2017)−36−48−14Stimuli: general demandsHayashi et al. (2014)−48−54−14Stimuli: visual/linguistic contentPurcell et al.…”
Section: Introductionunclassified
“…Many neuroimaging studies on the developing brain have used the adult template and demonstrated that using the adult template did not affect the results of their analyses (63)(64)(65)(66)(67). Moreover, the standard adult SPM template is regarded as a good tool to compare or combine the results from previous studies across different age groups (68)(69)(70).…”
Section: Regional Vbm Analysismentioning
confidence: 99%